Respuesta :
[tex]\\ \sf\longmapsto 5.47-(-x)=9.24[/tex]
[tex]\\ \sf\longmapsto 5.47+x=9.24[/tex]
[tex]\\ \sf\longmapsto x=9.24-5.47[/tex]
[tex]\\ \sf\longmapsto x=3.77[/tex]
Option H
Answer:
[tex] \bf \: Option \: H[/tex]
[tex]\boxed{\tt x = 3.77}[/tex]
Step-by-step explanation:
Given equation :-
[tex]\sf \implies5.47 - ( - x) = 9.24[/tex]
We need to find the value of x.
Solution :-
[tex]\sf \implies5.47-(-x) = 9.24[/tex]
As we know that "-'' and "-" equals to "+".
So rewrite "-(-x) as "+x".
[tex]\sf \implies5.47 \bold{ + }x = 9.24[/tex]
This equation may be rewritten as,
[tex]\sf \implies \: x + 5.47 = 9.24[/tex]
[tex]\rm \: Subtract \: 5.47 \: from \: both \: sides : [/tex]
[tex]\sf \implies \: x + 5.47 - 5.47 = 9.24 - 5.47[/tex]
First, simplify the LHS :-
[tex]\sf \implies \: x+0 = 9.24 - 5.47[/tex]
[tex]\sf \implies \: x = 9.24 - 5.47[/tex]
Now, Simplify The RHS :-
[tex]\sf \implies \: x = 3.77[/tex]
Hence, the value of x is :
[tex]\boxed{\tt x = 3.77}[/tex]
Option H is correct!
Let's check whether the equation is TRUE or NOT.
So for that we need to plug the value of x we got on this equation :-
[tex]\sf \implies5.47-(-x) = 9.24[/tex]
[tex] \rm \: Plug \: the \: value ( \: x \: = 3.77):-[/tex]
[tex]\sf \implies5.47-(-3.77) = 9.24[/tex]
[tex] \rm \: Simplify \: the \: LHS \: of \: this \: equation :-[/tex]
[tex]\sf \implies \: 5.47 + 3.77 = 9.24[/tex]
Add 5.47 and 3.77 which results to :-
[tex]\sf \implies9.24 = 9.24[/tex]
[tex]\sf \implies \: LHS = RHS[/tex]
HENCE,this equation is TRUE.
We are done!
______________________________________
I hope this helps!